1990
DOI: 10.1111/j.1432-1033.1990.tb19367.x
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phospholipid metabolism in human platelets stimulated by ADP

Abstract: ADP-induced changes in inositol phospholipids, phosphatidic acid and inositol phosphates of human platelets have been studied in detail, using not only 32P labelling, but also by examining changes in amounts of the phospholipids, their labelling with [3H]glycerol and their specific radioactivities ; changes in the labelling of inositol phosphates in platelets prelabelled with [3H]inositol were also measured. During the early (10 s) stage of reversible ADP-induced primary aggregation in a medium containing fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 30 publications
3
20
1
1
Order By: Relevance
“…Packham et al [18] have previously shown that under these conditions the platelets aggregate reversibly, but do not secrete the contents of storage granules or form thromboxane A,. These experiments indicate that two signal transduction events are necessary to cause the decreases in PtdInsP, and PtdInsP that we have detected at 10 s in ADP-stimulated human platelets (in these experiments and [19]). Initially, ADP stimulation causes shape change and activates receptors for fibrinogen (presumably GPIIb/IIIa).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Packham et al [18] have previously shown that under these conditions the platelets aggregate reversibly, but do not secrete the contents of storage granules or form thromboxane A,. These experiments indicate that two signal transduction events are necessary to cause the decreases in PtdInsP, and PtdInsP that we have detected at 10 s in ADP-stimulated human platelets (in these experiments and [19]). Initially, ADP stimulation causes shape change and activates receptors for fibrinogen (presumably GPIIb/IIIa).…”
Section: Discussionmentioning
confidence: 64%
“…In previous studies, with both rabbit [35] and human [19] platelets, we have presented evidence that the decreases in PtdInsP, and PtdInsP detected at 10 s are unlikely to be due to the action of phospholipase C on PtdInsP,, based on the absence of increases in (a) inositol trisphosphate labelling in platelets prelabelled with ['Hlinositol and (b) PtdOH specific radioactivity in platelets prelabelled with ['Hlglycerol. The inositol phosphates were not examined in this study but, consistent with the previous studies 119, 351, the specific radioactivity of PtdOH labelled with [3H]glycerol did not increase at 1 0 s in response to ADP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ADP is clearly able to induce PLC activation under our experimental conditions, as revealed by measurement of PKC activation (Fig. 1) and intracellular Ca 2ϩ mobilization (data not shown), we have been unable to reliably measure agonistinduced accumulation of inositol phosphates or DAG, probably because of the weakness of the response (data not shown), as suggested by early studies (30). Therefore, we took advantage from the evidence that the P2Y12 receptor is also implicated in PKC activation induced by U46619, which is a stronger activator of PLC.…”
Section: The P2y12 Receptor Does Not Influence G Q -Mediated Activatimentioning
confidence: 65%
“…ADP'nin trombositlerde PA düzeyi üzerine etkisini araştıran gruplardan bir kısmı PA düzeyinin arttığını, bir kısmı ise değişmediğini bildirmektedir. Ayrıca türler arasında da farklar olduğu vurgulanmaktadır (71). Bir çok araştırıcı ADP ile uyarılan trombositlerde İP oluşumunu gösterememiştir .…”
Section: C-gmpunclassified